Triglyceride peroxidation progression in lipid droplets of hepatocytes in nonalcoholic steatohepatitis - Kota Saito; Yuta Matsuoka; Masami Abe; Nao Kato; Kazushi Morimoto; Ken-ichi Yamada (Bioscientifica, 2024)
Objective: Nonalcoholic steatohepatitis is a chronic liver disease caused by the progression of hepatocellular death and inflammation from simple steatosis. However, the pathogenesis of this disease remains unclear. Lipid peroxidation is one of the most critical factors in the development of nonalcoholic steatohepatitis; however, oxidised lipids - the products of lipid peroxidation - are insufficiently analysed. Here, we comprehensively analysed oxidised lipids in the liver during nonalcoholic steatohepatitis development in a choline-deficient, l-amino acid-defined, high-fat diet-fed mouse model. Methods: Liver from C57BL/6J mice, fed a standard diet or a choline-defi cient l-amino acid-defined high-fat diet for 1, 3, or 6 weeks, were collected to ev aluate fibrosis, steatosis, inflammation, liver injury, and oxidised lipid production and to observe the suppression of these parameters upon vitamin E administration. In addition, organellar localisation of lipid peroxidation was assessed using fluorescence imaging. Finally, a mitochondria-targeted antioxidant was administered to model mice to investigate the mechanism underlying lipid peroxidation. Results: We found an accumulation of oxidised triglycerides in the earl y stages of nonalcoholic steatohepatitis. Furthermore, our data indicate that oxidised triglycerides are generated by lipid peroxidation in lipid droplets due to mi tochondria-derived reactive oxygen species. Conclusion: These results suggest the importance of lipid droplet peroxidation in the progression of nonalcoholic steatohepatitis and may contribute to the development of therapeutic methods for nonalcoholic steatohepatitis in the future. Significance statement We demonstrate the specific and early occurrence of lipid peroxidation in nonalcoholic steatohepatitis pathogenesis and propose a previously unknown mechanism of disease progression.